Analisis Bibliometrik Resolusi Konflik di Sekolah Dasar Menggunakan Vosviewer Indexed By Google Scholar - Altaftazani, Deden Herdiana; Rahayu, Galih Dani Septiyan Rahayu; Fauzi, Muhammad Rizal Fauzi (P2M STKIP Siliwangi, 2023)
Conflict resolution is a skill that needs to be developed at this time, especially for elementary school students. Conflict resolution can help students in dealing with various problems that occur in their daily lives. This study aims to find out the development of research on conflict resolution in elementary schools by conducting a bibliometric analysis of bibliographic data on research articles indexed by Google Scholar by combining analysis in terms of the distribution of bibliometric maps using VOSviewer software. The data filtering process was carried out based on the keywords "conflict resolution and primary education" contained in the topics, titles, keywords, and abstracts. The search was carried out on articles published from 2000 to 2022. From the search results, 24 relevant articles were obtained. The results showed that most research on conflict resolution in elementary schools was conducted in 2010. Research on conflict resolution in elementary schools is still very rare. Looking at these data, the opportunity to develop research on conflict resolution in elementary schools is huge. Therefore, this research is expected to provide references and considerations in seeking further research fields, especially those related to conflict resolution in elementary schools